Biogeochemical evolution of deep-sea sediments in Iceberg Alley (Scotia Sea) since the Miocene and implications for carbon and iron cycling - Andrew W. Dale; Klaus Wallmann; Bridget Kenlee; Michael E. Weber; Timothy W. Lyons; Marcus Gutjahr (Geochimica et Cosmochimica Acta, 2026)

Tissue metal concentrations and toxicity in wild turkeys following chronic exposure to mining-contaminated soils in southeast Missouri, USA - Katrina K. Knott; Danielle Cleveland; Jason L. Isabelle; Nicole M. Nemeth; Emma Coleman; Michelle Seers; Nicholas Sievert; Emily Sinnott; Timothy Lyons; Jeff Wenzel; Paul Blanchard (Ecotoxicology, 2026)

Transient glacio-eustatic fall and its climato-environmental effects during the Frasnian-Famennian transition - Thomas J. Algeo; Mariano N. Remírez; He Zhao; Lorenz Schwark; Gwyneth Gordon; Ariel Anbar; Steven Bates; Timothy Lyons; D. Jeffrey Over; Brad Sageman (Global and Planetary Change, 2026)

Chromium isotope fractionation in the redox-stratified Chesapeake Bay - Debbrota Mallick; Xiangli Wang; Marzia Miletto; Jeffrey W. Krause; Daniel C. Ohnemus; Noah J. Planavsky; George W. Luther; Timothy W. Lyons; Bradley M. Tebo (Applied Geochemistry, 2026)

Environmental drivers of foraging by deep-diving cetaceans: Roles of mesoscale oceanography and light-driven cycles - Thomas A. Clay; Gemma Carroll; Megan A. Cimino; Jennifer L. Miksis-Olds; Katie A. Kowarski; Anthony P. Lyons; Peter I. Miller; Timothy S. Moore; Joseph D. Warren; Elliott L. Hazen (Progress in Oceanography, 2025)

Sulfur cycling at two Mars-relevant saline lakes underscores the importance of dynamic metabolic substrate concentrations for isotopic biosignatures - Christopher J. Tino; Serhat Sevgen; Alec M. Hutchings; Jaxon Dii Horne; Liam E. Walters; Timothy W. Lyons; Benjamin M. Tutolo (Geochimica et Cosmochimica Acta, 2025)

Precision forestry in actively managed loblolly pine plantations: Leaf area index response one growing season following a variable-rate fertilization - Chris W. Cohrs; Al Lyons; Timothy J. Albaugh; David R. Carter; Otávio C. Campoe; Rafael A. Rubilar; Matthew Sumnall; Andrew Trlica; Mark V. Corrao; Simerjeet Virk; Rex Lester; Rachel L. Cook (Forest Ecology and Management, 2025)

TNF-α Pathway Activation and Altered microRNA Expression in Peripheral Blood-Derived Endothelial Colony-Forming Cells: Insights into Diabetes-Induced Dysfunction - Yaqiong Liu; Caomhán J. Lyons; Alan Keane; Stuart McKeown; Edoardo Pedrini; Michael Creane; Nadeem Soomro; Alicja Straszewicz; Tomás Griffin; Alan Stitt; Timothy O’Brien (Stem Cell Reviews and Reports, 2025)

Citation for the 2024 Goldschmidt to Donald E. Canfield - Timothy W. Lyons (Geochimica et Cosmochimica Acta, 2025)

Middle Ordovician paleoenvironmental evolution of the western Laurentian carbonate platform: Evidence for persistent oxygenation of the shallow ocean and implications for biodiversification - Charles W. Diamond; Matthew R. Saltzman; Timothy W. Lyons; Cole T. Edwards (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Long-range transport of dust enhances oceanic iron bioavailability - Bridget Kenlee; Jeremy D. Owens; Robert Raiswell; Simon W. Poulton; Silke Severmann; Peter M. Sadler; Timothy W. Lyons (Frontiers in Marine Science, 2024)
Wind-borne dust supply of iron (Fe) to the oceans plays a crucial role in Earth’s biogeochemical cycles. Iron, a limiting micronutrient for phytoplankton growth, is fundamental in regulating ocean primary productivity and in turn the global carbon cycle. The flux of bioavailable Fe to the open ocean affects oscillations in atmospheric CO 2 due to its control on inorganic carbon fixation into organic matter that is eventually exported to the sediments. However, the nature of dust-delivered Fe to the ocean and controls on its bioavailability remain poorly constrained. To evaluate the supply of wind-borne bioavailable Fe and its potential impact on Fe-based climate feedbacks over the last 120,000 years, we examine sediment profiles from four localities that define a proximal to distal transect relative to Saharan dust inputs. Bulk δ 56 Fe isotope compositions (average = -0.05‰) and Fe T /Al ratios suggest crustal values, thus pointing to a dominant dust origin for the sediments at all four sites. We observed no variability in grain size distribution or in bioavailable Fe supply at individual sites as a function of glacial-versus-interglacial deposition. Importantly, there is no correlation between sediment grain size and Fe bioavailability. Spatial trends do, however, suggest increasing Fe bioavailability with increasing distance of atmospheric transport, and our sediments also indicate the loss of this Fe and thus potential bioavailability utilization once deposited in the ocean. Our study underscores the significance of Fe dynamics in oceanic environments using refined speciation techniques to elucidate patterns in Fe reactivity. Such insights are crucial for understanding nutrient availability and productivity in various ocean regions, including the Southern Ocean, where wind-delivered Fe may play a pivotal role. It is expected that dust delivery on glacial-interglacial timescales would be more pronounced in these high-latitude regions. Our findings suggest that studies linking Fe availability to marine productivity should benefit significantly from refined Fe speciation approaches, which provide insights into the patterns and controls on Fe reactivity, including atmospheric processing. These insights are essential for understanding the impacts on primary production and thus carbon cycling in the oceans and consequences for the atmosphere.

Linking carbon cycle perturbations to the Late Ordovician glaciation and mass extinction: A modeling approach - Junpeng Zhang; Chao Li; Yangyang Zhong; Xuejin Wu; Xiang Fang; Mu Liu; Daizhao Chen; Benjamin C. Gill; Thomas J. Algeo; Timothy W. Lyons; Yuandong Zhang; Hui Tian (Earth and Planetary Science Letters, 2024)

Productivity and organic carbon loading control uranium isotope behavior in ancient reducing settings: Implications for the paleoredox proxy - Randolph L. Rutledge; Geoffrey J. Gilleaudeau; Mariano N. Remírez; Alan J. Kaufman; Timothy W. Lyons; Steven Bates; Thomas J. Algeo (Geochimica et Cosmochimica Acta, 2024)

A volatile sulfur sink aids in reconciling the sulfur isotope mass balance of closed basin lakes - Antoine Crémière; Christopher J. Tino; Maxwell E. Pommer; Xingqian Cui; Matthew Roychowdhury; Roger E. Summons; Alex Sessions; J. Fredrick Sarg; Timothy W. Lyons; Jess F. Adkins (Geochimica et Cosmochimica Acta, 2024)

Network Analysis Reveals Species-Specific Organization of Microbial Communities in Four Co-Occurring Elasmobranch Species along the Georgia Coast - Kady Lyons; Christine N. Bedore; Aaron B. Carlisle; Lauren Moniz; Timothy L. Odom; Rokeya Ahmed; Stephen E. Greiman; Ryan M. Freedman (Fishes, 2024)
Comparing co-occurring species may provide insights into how aspects of ecology may play a role in influencing their microbial communities. During the 2019 commercial shrimp trawl season off coastal Georgia, swabs of skin, gills, cloaca, and gut were taken for three species of batoids (Butterfly Ray, Bluntnose Stingray, and Atlantic Stingray) and one shark species (Atlantic Sharpnose) for high-throughput sequencing of the V4 region of the bacterial 16S rRNA gene. White muscle was analyzed for stable isotopes (δ13C and δ15N) to evaluate potential niche overlap in these four sympatric mesopredators. Significant differences were found in both δ13C and δ15N signatures across species, suggesting a degree of resource partitioning. When examined within tissue type, the host species had a weak effect on β-diversity for cloaca and skin, with no differences found for gill and gut samples. However, network analysis metrics demonstrated a stronger species-specific effect and distinct microbial community relationships were apparent between the shark and batoids, with the former having tighter networks for both internally- and externally-influenced tissues (gut/cloaca and skin/gills, respectively). Despite overlapping habitat use, species’ microbiomes differed in their organizational structuring that paralleled differences in stable isotope results, suggesting a mediating role of species-specific ecology on bacterial microbiomes.

Dynamic evolution of marine productivity, redox, and biogeochemical cycling track local and global controls on Cryogenian sea-level change - Chenyi Tu; Charles W. Diamond; Eva E. Stüeken; Mengchun Cao; Wen Pan; Timothy W. Lyons (Geochimica et Cosmochimica Acta, 2024)

A novel big-data perspective on earth system evolution - Hafida EL Bilali; Richard E. Ernst; Timothy W. Lyons; Andrey Bekker (International Geology Review, 2023)

Refined views of ancient ocean chemistry: Tracking trace element incorporation in pyrite framboids using atom probe tomography - Nicole Mae M. Atienza; Daniel D. Gregory; Sandra D. Taylor; Megan Swing; Daniel E. Perea; Jeremy D. Owens; Timothy W. Lyons (Geochimica et Cosmochimica Acta, 2023)

Tracing the sedimentary provenance of the Mesoproterozoic rocks from Taoudeni Basin (∼ 1.1 Ga) Mauritania: Evidence from Sm/Nd and elemental geochemistry - Mohamed Ghnahalla; Olabode M. Bankole; Ahmed Abd Elmola; Marc Poujol; Claude Fontaine; Mohamed Salem Sabar; Alain Trentesaux; Chenyi Tu; Timothy W. Lyons; Abderrazak El Albani (Precambrian Research, 2023)

Earth’s surface oxygenation and the rise of eukaryotic life: Relationships to the Lomagundi positive carbon isotope excursion revisited - Mojtaba Fakhraee; Lidya G. Tarhan; Christopher T. Reinhard; Sean A. Crowe; Timothy W. Lyons; Noah J. Planavsky (Earth-Science Reviews, 2023)

Organic matter sulfurization and organic carbon burial in the Mesoproterozoic - Morgan Reed Raven; Peter W. Crockford; Malcolm S.W. Hodgskiss; Timothy W. Lyons; Christopher J. Tino; Samuel M. Webb (Geochimica et Cosmochimica Acta, 2023)

Manganese oxides, Earth surface oxygenation, and the rise of oxygenic photosynthesis - Leslie J. Robbins; Mojtaba Fakhraee; Albertus J.B. Smith; Brendan A. Bishop; Elizabeth D. Swanner; Caroline L. Peacock; Chang-Le Wang; Noah J. Planavsky; Christopher T. Reinhard; Sean A. Crowe; Timothy W. Lyons (Earth-Science Reviews, 2023)

Early diagenetic processes in an iron-dominated marine depositional system - Maria C. Figueroa; Sebastiaan J. van de Velde; Daniel D. Gregory; Sydnie Lemieux; Jeana Drake; Tina Treude; Nathaniel Kemnitz; William Berelson; Konstantin Choumiline; Steven Bates; Ravi Kukkadapu; Marilyn Fogel; et al. (Geochimica et Cosmochimica Acta, 2023)

Unstable intraguild predation causes establishment failure of a globally invasive species - Quenton M. Tuckett; Amy E. Deacon; Douglas Fraser; Timothy J. Lyons; Katelyn␣M. Lawson; Jeffrey E. Hill (Ecology, 2021)
Biotic resistance is often posited, but rarely known, to be the cause of invasion failure. Competition and predation are the most frequently identified processes that may prevent or limit the establishment of nonnative species. Interactions between nonnative and native species that involve intraguild predation (IGP) are very common in nature, although theory predicts most IGP systems should be unstable and lead to extinction. If this prediction is true, the frequency of invasion failures due to IGP may be underappreciated because of their fleeting nature and, thus, studies of unstable IGP systems are lacking, despite the opportunities they offer for understanding the factors affecting their unstable dynamics. We investigated a failed invasion involving an IGP relationship. In Florida, the guppy ( Poecilia reticulata ), a worldwide invader, fails to establish in the presence of eastern mosquitofish ( Gambusia holbrooki ). We tested whether and how resident mosquitofish cause guppy invasion failure using replicated mesocosm and aquarium trials. Both the predator and competitor components of the IGP relationship were strongly asymmetrical, with large impacts on guppies. We identified two effects, direct consumption of neonates and aggressive interference competition, that limited survival and recruitment. The highly unstable nature of this IGP relationship is the primary cause of the failure of the guppy to establish in Florida. Our study shows that the transient nature of an ephemeral IGP relationship can yield important insights into the underlying causes of invasion failure, including the role of strong biotic resistance.

Risk screen of lionfishes, Pterois, Dendrochirus, and Parapterois, for southeastern United States coastal waters of the Gulf of Mexico and Atlantic Ocean - Timothy J. Lyons; Quenton M. Tuckett; Allison Durland Donahou; Jeffrey E. Hill (Biological Invasions, 2020)

Dissolved Inorganic Carbon Pump in Methane-Charged Shallow Marine Sediments: State of the Art and New Model Perspectives - Sajjad A. Akam; Richard B. Coffin; Hussain A. N. Abdulla; Timothy W. Lyons (Frontiers in Marine Science, 2020)

Data quality and quantity for invasive species: A case study of the lionfishes - Timothy J. Lyons; Quenton M. Tuckett; Jeffrey E. Hill (Fish and Fisheries, 2019)
Predicting invasion risk involves inherent uncertainty when data on biological and ecological characteristics are lacking. To combat data gaps, assessors are required to use information from secondary sources, further reducing predictive accuracy. Lionfish in the subfamily Pteroinae have invasion history in the Western Atlantic Ocean and Mediterranean Sea, raising concern that other species of globally traded lionfish may pose risks similar to the invasive complex comprised of the red lionfish ( Pterois volitans , Scorpaenidae) and devil firefish ( Pterois miles , Scorpaenidae). We conducted a standardized literature review of 18 species in the genera Pterois , Dendrochirus , and Parapterois to (a) characterize the volume and composition of literature addressing the invasive complex pre‐establishment and pre‐spread, and compare it to the body of literature that has been generated post‐spread and impact, (b) compare the volume and composition of literature addressing other members of Pteroinae to the invasive complex, and (c) evaluate data quality addressing the Pteroinae by characterizing literature used to generate biological profile reports during a risk screening protocol. Little data were available for the invasive complex prior to introduction and focused primarily on the composition or effects of venom. Following introduction, there was a considerable time lag in research effort. Post‐spread, research effort increased rapidly. We identify similar data deficiencies for other species of lionfish that have not been reported outside of their native ranges. While proactive management is gaining support as an effective framework, it is important to understand data limitations and their resulting uncertainties, which leads to more informed proactive management.

Food habits and relative abundances of native piscivores: implications for controlling common carp - Todd D. VanMiddlesworth; Greg G. Sass; Bradley A. Ray; Timothy W. Spier; John D. Lyons; Nerissa N. McClelland; Andrew F. Casper (Hydrobiologia, 2017)

The violation of Fitts’ Law: an examination of displacement biases and corrective submovements - James W. Roberts; Jarrod Blinch; Digby Elliott; Romeo Chua; James L. Lyons; Timothy N. Welsh (Experimental Brain Research, 2016)

Premaxillae of the Extinct Megalonychid Sloths Acratocnus, Neocnus, and Megalonyx, and their Phylogenetic Implications (Mammalia, Xenarthra) - Lauren M. Lyon; Chelsea Powell; H. Gregory McDonald; Timothy J. Gaudin (Journal of Mammalian Evolution, 2016)

Hepatic Biomarkers in Diabetes as Modulated by Dietary Phytochemicals - Arpita Basu; Paramita Basu; Timothy J. Lyons (Exposure and Health, 2016)

Strawberry As a Functional Food: An Evidence-Based Review - Arpita Basu; Angel Nguyen; Nancy M. Betts; Timothy J. Lyons (Critical Reviews in Food Science and Nutrition, 2014)

Comparative genomics reveals functional transcriptional control sequences in the Prop1 gene - Robert D. Ward; Shannon W. Davis; MinChul Cho; Constance Esposito; Robert H. Lyons; Jan-Fang Cheng; Edward M. Rubin; Simon J. Rhodes; Lori T. Raetzman; Timothy P. L. Smith; Sally A. Camper (Mammalian Genome, 2007)

Paradigm Lost, Paradigm Found: The Black Sea-Black Shale Connection as Viewed from the Anoxic Basin Margin - Timothy Lyons; Michaele Kashgarian (Oceanography, 2005)